A river ran wild : an environmental history - Cherry, Lynne (San Diego : Harcourt Brace Jovanovich, 1992)
An environmental history of the Nashua River, from its discovery by Indians through the polluting years of the Industrial Revolution to the ambitious clean-up that revitalized it.
"A Gulliver Green book."
Keywords: Water quality -- Nashua River (Mass. and N.H.) -- History -- Juvenile literature; Nature -- Effect of human beings on -- Nashua River (Mass. and N.H.) -- History -- Juvenile literature; Indians of North America -- Nashua River (Mass. and N.H.) -- History -- Juvenile literature; Nature -- Effect of human beings on; Nashua River (Mass. and N.H.) -- History -- Juvenile literature; Nashua River Valley (Mass. and N.H.) -- History -- Juvenile literature; Nashua River (Mass. and N.H.) -- History